تأثير البارمترات الحاكمة على أداء توربين ريحي ذو محور أفقي، للوصول إلى أفضل مردود ممكن عند سرعات الرياح المنخفضة - فريد أبو حامد (Tishreen University, 2019)
ينطلق البحث من فكرة أن كثيراً من شركات تصنيع التوربينات الريحية لا تدخل في حساباتها سرعة الرياح المنخفضة في التصميم الأساسي للتوربينات، وتعتمد في تصميمها على سرعات كبيرة لا تبلغها الرياح في منطقتنا العربية إلا لساعات معدودة على مدار السنة باستثناء بعض المناطق، الأمر الذي يستوجب بذل جهود ملموسة لتطوير صناعة توربينات الرياح الصغيرة التي تعمل بسرعات منخفضة بما يتوافق مع المعطيات الريحية والمتطلبات المحلية. إن الهدف العام من تصميم توربين ريحي مثالي هو إمكانية استخلاص طاقة الرياح بأقل كلفة ممكنة للمنظومة، وهذا الهدف قد يختلف بعض الشيء عن تصميم توربين ريحي مثالي لسرعة رياح منخفضة، وبذلك سيواجه التصميم تحديات أكبر تتمثل بانخفاض الأداء وكذلك مشكلة الإقلاع. لذلك فان معظم العوامل المؤثرة قد تم دراستها خلال البحث وأدخلت القيم المثالية لها في التصميم الأساسي، وبما أن التوربين يمكن أن يواجه ظروفاً مختلفة عن الواقع التصميمي فقد تمت دراسة أداء التوربين عملياً من خلال السيطرة والتحكم بقيم معظم البارمترات المؤثرة، وبيان تأثير ذلك على بعضها الآخر وكذلك على فعالية التوربين في استخلاص الطاقة ومن أهم هذه العوامل: عدد ريش الدوار (N) ونسبة الصلابة (σ)، وزاوية ميل الريشة (ө)، ونسبة سرعة الطرف (λ)، والحمل المسلط (P). This study has started from the idea that many of the manufacturers of wind turbines do not take into account the low speed of winds in the basic design of wind turbines, as they base their design on high speeds that winds in the Arab region cannot reach but only for a few hours throughout the year, except for some areas. This involves some real efforts to be exerted to improve the industry of small wind turbines operating at low speeds in accordance with wind data and local requirements. The general purpose of designing an ideal wind turbine is to see the possibility of extracting wind energy at low cost. This target may differ slightly from the design of an ideal wind turbine for low speed winds, thus facing bigger challenges represented in the starting problem and the decrease of performance. Therefore, most factors affecting the performance have been studied through this research and the relevant ideal values have been introduced in the basic design. Since the turbine may face performance conditions different from the design environment, the turbine performance has been practically studied through controlling the values of most affecting parameters and their effect on each other and on turbine efficiency for extracting energy. The main factors that influence efficiency are: the number of rotor blades (N), rigidity proportion (), the inclination (), the rate of edge speed (), and the applied load (P).